(untitled) (Journal of Medical & Health Sciences Review, 2025)
Returning to sport after an injury can be a challenging journey for many athletes. This cross-sectional study explored how post-traumatic footballers perceive their sports performance after completing rehabilitation and resuming play. Conducted over six months in Fame Football Club Lahore, the study included 127 footballers aged 18–35 years, selected through non-probability convenience sampling. All participants had undergone at least six months of rehabilitation and were medically cleared to return to football. Data were gathered using the Sport Performance Perceptions Scale (SPPS) and analyzed with SPSS version 25. Overall, the results showed that players had a moderately high sense of performance, with the strongest perceptions in Mastery and Development and the weakest in Recovery and Injury Prevention. These insights suggest that although athletes feel confident about their skills and growth, they see room for improvement in how they recover and prevent future injuries. The findings underline the need to include psychological and educational support within post-injury rehab programs to help athletes maintain their performance and stay in the game longer.